Upper respiratory illnesses in athletes: Are mucosal immunity and cytokine responses key risk factors? - Gleeson, M.; Bishop, N. C. (Exercise and Sport Sciences Reviews, 2013)
Infection incidence among athletes is highest during periods of intensified training and competition and after strenuous long-distance events. Which aspects of depressed immune function are responsible for this increased infection risk are not known, but our hypothesis is that lower salivary immunoglobulin A (IgA) secretion and a higher antiinflammatory cytokine response to antigen exposure are key determinants of infection risk.